please solve

f(x) = 64x^4 - 192x^3 + x^2 - 3x

f(x) = x(64x^3 - 192x^2 + x - 3)

f(x) = x( 64x^2(x - 3) + 1(x - 3) )

f(x) = x(x - 3)(64x^2 + 1)

f(x) = x(x - 3)((8x)^2 – (i^2))

f(x) = x(x - 3)(8x – i)(8x + i)

please solve

Tutors, please sign in to answer this question.

Westford, MA

f(x) = 64x^4 - 192x^3 + x^2 - 3x

f(x) = x(64x^3 - 192x^2 + x - 3)

f(x) = x( 64x^2(x - 3) + 1(x - 3) )

f(x) = x(x - 3)(64x^2 + 1)

f(x) = x(x - 3)((8x)^2 – (i^2))

f(x) = x(x - 3)(8x – i)(8x + i)

Vernon Hills, IL

f(x)=64x^{4}-192x^{3}+x^{2}-3x=x(64x^{3}-3*64x^{2}+x-3)=x[64x^{2}(x-3)+(x-3)]=x(x-3)(64x^{2}+1)

Daniel H.

Harvard & Law School Graduate - Master Tutor for Tests/Academics

New York, NY

4.9
(45 ratings)

Steven L.

Cornell Alum - Enthusiast in Math and Science (Regents, SAT/ACT, AP)

Fresh Meadows, NY

4.9
(140 ratings)

Michael E.

H.S. Mathematics Tutor (Certified NJ Teacher)

Saddle Brook, NJ

5.0
(113 ratings)

- Algebra 4565
- Algebra Help 938
- Algebra 1 3758
- College Algebra 977
- Algebra Word Problem 2306
- Algebra Question 222
- Math 8626
- Algebra 2 3157
- Math Help 4868
- Algebra 2 Question 475